Analysis of surface recombination in nanowire array solar cells - Yu, Shuqing; Roemer, Friedhard; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2012)
In this work, microscopic three-dimensional (3D) simulations were performed on nanowire array solar cells to study the impact of surface recombination on the photovoltaic performance. Both axially and radially arranged p-n junction in III-V based structures were taken into consideration. From the cases with surface recombination velocity varying from 1e3cm/s to 1e6cm/s, the core-shell nanowire was found to provide better tolerance for surface recombination. The difference of surface recombination within the axial and core-shell structures is explained by analyzing the relevent minority carrier density, followed by a discussion on the impact of surface recombination on the performance of nanowires as photovoltaic devices. © 2012 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Carrier transport properties; Nanowire; Photovoltaics; Semiconductor; Solar cell